Czynniki warunkujące zysk netto banków spółdzielczych - Kowalski, Olaf; Balina, Rafał; Różyński, Jerzy (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
The aim of the study was to identify the key factors determining the level of net profit of polish cooperative banks in the period 2005–2010. Studies have shown that the key factors influencing the net profit realized by cooperative banks were variables defining the basic funds, amount of employees and the amount of loans granted.